(untitled) (Scientia Agropecuaria, 2023)
Cocoa (Theobroma cacao L.) is one of the most important economic crops worldwide. The propagation of elite varieties of cocoa has been achieved through somatic embryogenesis, but still one of the main limitations is the low rates of embryo formation, which is a genotype-dependent trait. Manipulation of transcription factors (TFs) such as BABY BOOM (BBM) promotes the transition of cocoa somatic cells from the vegetative to the embryonic state. This work validated the use of clonal cocoa leaves cv. IMC-67 to induce somatic embryogenesis, overcoming their recalcitrant limitation with the help of the introduction of TF-BBM from Arabidopsis thaliana (AtBBM). The vectors were constructed by the Gateway system using the donor vector pENTR/D-TOPO and the expression vector pk7WG2. The overexpression vector pk7WG2:AtBBM was obtained, allowing successful transformation into Agrobacterium tumefaciens GV3101. The AtBBM gene was characterized (1755 base pairs), and its expression was observed in the formation of embryogenic calluses in cocoa leaves. Overexpression of AtBBM allowed the obtainment of a 92% response in the formation of embryogenic callus in cocoa leaves with Agrobacterium-mediated vacuum infiltration and overexpression of the pk7WG2:AtBBM vector. This high transformation efficiency reached with the insertion of the overexpression vector provides validation of transient response of the TF AtBBM in the formation of embryogenic calluses in cocoa leaves of the IMC-67 clone. Through this methodology, it is possible to continue with studies of gene overexpression, insertion, silencing, and gene editing in Peruvian cocoa.